Overexpression of an NF-YC2 gene confers alkali tolerance to transgenic alfalfa (Medicago sativa L.) - Yu, Jinqiu; Yuan, Yuying; Zhang, Wenkai; Song, Tingting; Hou, Xiangyin; Kong, Lingzelai; Cui, Guowen (Frontiers in Plant Science, 2022)
Alkali stress is the primary factor limiting plant growth and quality worldwide. NF-YC transcription factors (TFs) respond to abiotic stress by activating gene expression. However, the biological function of NF-YC TFs in alfalfa (Medicago sativa L.) is not clear. In this study, we identified and characterized an NF-YC2 gene from alfalfa. The open reading frame of MsNF-YC2 is 879 bp, encoding a protein of 292 amino acids with a molecular mass of 32.4 kDa. MsNF-YC2 exhibited tissue-specific expression and was induced in response to various abiotic stresses, including drought, salt, and alkali stress in alfalfa. An MsNF-YC2 overexpression vector was constructed and transformed into alfalfa. Overexpression of MsNF-YC2 improved the alkali tolerance of the transgenic plants. Under alkali stress, compared with wild-type (WT) plants, the transgenic plants also showed higher activities of antioxidant enzymes; lower levels of hydrogen peroxide (H2O2), superoxide anion (O2−), and malondialdehyde (MDA); and higher proline (Pro) levels. Transcriptomic analysis revealed that MsNF-YC2 overexpression affected the response to plant hormone signal transduction and photosynthesis-related genes under both normal and alkali stress conditions. Taken together, these results indicate that MsNF-YC2 genes can modulate alkali stress tolerance through the regulation of plant growth and the activation of gene expression in alfalfa.